2019
DOI: 10.3389/fpsyt.2019.00534
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Psychiatry—How Computational Neuroscience Can Help to Understand the Complex Mechanisms of Mental Disorders

Abstract: The brain is the most complex of human organs, and the pathophysiology underlying abnormal brain function in psychiatric disorders is largely unknown. Despite the rapid development of diagnostic tools and treatments in most areas of medicine, our understanding of mental disorders and their treatment has made limited progress during the last decades. While recent advances in genetics and neuroscience have a large potential, the complexity and multidimensionality of the brain processes hinder the discovery of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 156 publications
1
20
0
Order By: Relevance
“…GWAS studies, such as Ripke et al [83], have identified numerous variants associated with psychiatric disorders, however, we know very little about their functional effects. As we have argued before [63,62], the modelling framework presented in this study is ideally suited to build hypotheses about their effects and to make experimentally testable predictions. To be more specific, the biophysically detailed model used here can provide very specific associations between genetic variants and phenotypes, while explicitly revealing the cellular properties through which the two are mechanistically linked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GWAS studies, such as Ripke et al [83], have identified numerous variants associated with psychiatric disorders, however, we know very little about their functional effects. As we have argued before [63,62], the modelling framework presented in this study is ideally suited to build hypotheses about their effects and to make experimentally testable predictions. To be more specific, the biophysically detailed model used here can provide very specific associations between genetic variants and phenotypes, while explicitly revealing the cellular properties through which the two are mechanistically linked.…”
Section: Discussionmentioning
confidence: 99%
“…[99]). Importantly, recent advances in computational modelling allow for the integration of knowledge about genetic contributions to ion channels and excitability and can be used to predict changes to macroscopic electroencephalography (EEG) or magnetoencephalography (MEG) signals ( [35,107,60], for a review of this emerging subfield of computational psychiatry see [62]). For example, simulations of a detailed model of tufted layer 5 pyramidal cells have recently been used to predict the effect of SCZ-associated variants of ion channel-encoding genes on neural activity in the delta frequency band [63].…”
Section: Introductionmentioning
confidence: 99%
“…EEG and, later, MEG signals have been an important part of neuroscience for a long time, but still very little is known about the neural origin of the signals [Cohen, 2017]. A better understanding of these signals could lead to important discoveries about how the brain works [Lopes da Silva, 2013;Uhlirova et al, 2016;Pesaran et al, 2018;Ilmoniemi and Sarvas, 2019], and provide new insights into mental disorders [Mäki-Marttunen et al, 2019a;Sahin et al, 2019]. This work lays some of the foundation for obtaining a better understanding of EEG/MEG recordings, by allowing easy calculation of the signals from arbitrary neural activity.…”
Section: Discussionmentioning
confidence: 99%
“…given that studies of healthy human brains necessarily are limited to non-invasive technologies [Lopes da Silva, 2013;Uhlirova et al, 2016;Cohen, 2017]. However, given all the valuable insights that could be gained from an increased understanding of non-invasive measurements of neural activity in humans, an important challenge in modern neuroscience is to build on the mechanistic insights from animal studies and use them for understanding non-invasive signals in humans [Lopes da Silva, 2013;Uhlirova et al, 2016;Cohen, 2017;Einevoll et al, 2019;Mäki-Marttunen et al, 2019a]. The approach for calculating EEG/MEG signals in this paper should therefore ideally be used in combination with animal studies simultaneously measuring multisite laminar LFP (and MUA) signals within cortex, as well as EEG/MEG signals (see for example Bruyns-Haylett et al [2017]) [Cohen, 2017].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation